An introduction to international criminal law and procedure / Robert Cryer [and others]. - Cryer, Robert (Cambridge University Press, 2010)
This market-leading textbook gives an authoritative account of international criminal law, and focuses on what the student needs to know - the crimes that are dealt with by international courts and tribunals as well as the procedures that police the investigation and prosecution of those crimes. The reader is guided through controversies with an accessible, yet sophisticated approach by the author team of four international lawyers, with experience both of teaching the subject, and as negotiators at the foundation of the International Criminal Court and the Rome conference. It is an invaluable introduction for all students of international criminal law and international relations, and now covers developments in the ICC, victims' rights, and alternatives to international criminal justice, as well as including extended coverage of terrorism. Short, well chosen excerpts allow students to familiarise themselves with primary material from a wide range of sources. An extensive package of online resources is also available.